Cardiovascular events and additional risk in hypertensive senior citizens - Rosimeire Fontes de Queiroz; Ângela Maria Alvarez; Alacoque Lorenzini Erdmann; Amanda Louise de Medeiros França; Cláudia Bezerra de Souza Pereira (Universidade Federal do Ceará, 2014)
The research aimed to investigate cardiovascular events and additional risks in hypertensive senior citizens' files attended in a Family Health Unit in Natal/RN, Brazil. This is a descriptive and documentary study developed based on 106 files from the Hiperdia Program registered from August to December 2012. The results showed that 13.2% were victims of Stroke, 10.37% of Acute Myocardial Infarction and 8.4% of other coronary diseases. In the cardiovascular risk stratification, 68.86% did not show additional risks, 31.11% were classified from low to very high risk for cardiovascular diseases. The results allow the planning of actions to take care of hypertensive senior citizens and are worthy of consideration for the Nursing professional practice, especially regarding the reorganization of its working process avoiding possible events.